2005
DOI: 10.1021/jp0500788
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure of Di-alkyl Chain Cationic/Nonionic Surfactant Mixtures:  Observation of Coexisting Lamellar and Micellar Phases and Depletion Induced Phase Separation

Abstract: The evolution of the microstructure and composition occurring in the aqueous solutions of di-alkyl chain cationic/nonionic surfactant mixtures has been studied in detail using small angle neutron scattering, SANS. For all the systems studied we observe an evolution from a predominantly lamellar phase, for solutions rich in di-alkyl chain cationic surfactant, to mixed cationic/nonionic micelles, for solutions rich in the nonionic surfactant. At intermediate solution compositions there is a region of coexistence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
43
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 31 publications
12
43
1
Order By: Relevance
“…The possibilities of coexistence between different morphologies of aggregates in one system have been discussed in the literature for copolymers or surfactants largely different in geometry, charge, and size. 38,39 More recently, Li et al showed the coexistence of copolymers in solution with similar composition (but with different PEG lengths: 10 and 18 units) that leads to the formation of coexisted mixed objects. Experimentally, 40 the authors found that small vesicles can coexist with a large amount of spheres for a specific mixing ratio R confirmed by molecular modelling.…”
Section: Coexisting Mixed Assembliesmentioning
confidence: 99%
“…The possibilities of coexistence between different morphologies of aggregates in one system have been discussed in the literature for copolymers or surfactants largely different in geometry, charge, and size. 38,39 More recently, Li et al showed the coexistence of copolymers in solution with similar composition (but with different PEG lengths: 10 and 18 units) that leads to the formation of coexisted mixed objects. Experimentally, 40 the authors found that small vesicles can coexist with a large amount of spheres for a specific mixing ratio R confirmed by molecular modelling.…”
Section: Coexisting Mixed Assembliesmentioning
confidence: 99%
“…Previous work has indicated that double-tailed cationic surfactants have been widely used as fabric softeners, antimicrobials, and antistatic agents [20] in many formulations because of their strong absorbability onto negative surfaces. APG and didecyldimethylammonium chloride (DDAC) mixtures, combining the advantages of pure APG and DDAC, are of particular interest and importance in the development of multi-functional disinfection and washing products [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, knowledge of the behavior of surfactant mixtures in solution and at the interface is very necessary. Among different types of mixed surfactant systems, cationic/nonionic surfactant mixtures are an important class because they are the major components of cosmetics, especially for hair and clothing conditioners [3][4][5][6]. Cationic surfactants are good fabric softeners, antimicrobials, and antistatic agents, while nonionic surfactants are biodegradable and mild in nature.…”
Section: Introductionmentioning
confidence: 99%